Oxygen Manifesto - "Mishra, Atulya" (New Delhi, 2019)
Oxygen manifesto is a story of the triumph of ordinary people over the might of the establishment in their battle to save the environment. Thatha lives in a remote and inaccessible part of Manipur and Ravi is a young IAS Officer from the Tamil Nadu Cadre. Circumstances bring them together and they create the most effective environmental movement the world has ever seen. They shun the politics of criticism and personal attacks and focus on establishing a new Polity based on the principles of environmental protection, habitat conservation, direct Civil action and democratic Decentralization. Oxygen manifesto is an engaging story about environmental degradation and the impact of the Anthropocene. It exposes the myth around wealth creation and the paradigm of economic growth. It also plants a development narrative that is environment-centric?an idea which is considered fringe in today?s times, but is bound to emerge as a mainstream thought in the future. The story also has an undercurrent of minimalism and Veganism, as opposed to consumerism and wasteful consumption. A novel concept of taxing Goods and Services based on their carbon and Water footprint has also been introduced by the writer. This is a must-read for anyone who cares about the future of human civilization.
Keywords: English Fiction